Engraftment of neural stem cells in the treatment of spinal cord injury - Martin M. Mortazavi; Mohammad Jaber; Nimer Adeeb; Aman Deep; Nicole Hose; Mona Rezaei; Salman Abbasi Fard; Babak Kateb; Parham Yashar; Mark A. Liker; R. Shane Tubbs (Translational Research in Anatomy, 2015)
Spinal cord injury is one of the main causes of disability in the young population. Based on the underlying pathological changes, many modalities of treatments have been trialed. However, the most promising so far, has been the replacement of lost cellular elements, using stem cells and non-stem cells transplantation. The route of cellular administration and engraftment into the site of injury is an important determining factor for functional outcome, and should be chosen to be safe and efficacious in human patients. Herein, we will review the underlying changes following spinal cord injury, and the possible routes of cellular transplantation. Keywords: Stem cell therapy, Engraftment, Intramedullary, Intrathecal, Intravascular, Intraventricular